E-bin: Smart Municipal Solid Waste Bin Designs - Sariman, Nurul Azra Nadia; Nathan, Shelena Soosay; Dahri, Nurul Atiqah; Abd Talib, Natasha Amira (Multidisciplinary Applied Research and Innovation, 2022)
Garbage disposal has become a topic of discussion for a decade. The management behind every garbage disposal was the Municipal solid waste management (MSW), as the MSW managed to collect and remove the garbage in residential areas, no matter in urban or rural areas of a country. Almost all the countries facing similar issues regarding garbage management, such as late collection of garbage and inefficient municipal solid waste management and disposal. This study provides a simple, innovative solution that integrates the Internet of Things (IoT) named as E-Bin. This project uses hardwares such as servo motor, ultrasonic sensors, LCD and RFID. Apart from that, Blynk Applications were used in notifying the authorities regarding overloaded garbage bins that needed immediate cleanup. E-Bin allows automatic lid opening through ultrasonic sensor, and also enables the users to collect reward points by throwing their rubbish into the dustbin. In conclusion, E-Bin provides a solution for better rubbish issue management. In the future, the smart dustbin can be upgraded into a garbage locator using GPS technology that helps the garbage collector to locate and collect garbage at its location.